Role of Orthopantamograph in Forensic Identification: A Retrospective Study Among Chennai Population - Sriraman Rajkumari; Kotha Nikitha; Sekar Monisha; Sekar Nishagrade; Balakrishnan Thayumanavan; Balasubramaniam Arunachala Murali (Wolters Kluwer Medknow Publications, 2019)
Context: Identification of unknown corpse can be established by their body features and belongings; when the features are distorted, it becomes a challenge for the forensic experts. Orthopantamograph (OPG) analysis is a simple, noninvasive, economic, and reliable method to sort for identification of the unidentified. Aim and Objective: The aim of this study was to assess the efficacy of OPG in age and sex determination. The objective of our study was to evaluate various measurements on the mandibular ramus and to correlate them with the age and sex of an individual. Settings and Design: A retrospective study was conducted using 150 OPGs that were taken in the Department of Oral Medicine and Radiology using Orthophos XG3 OPG machine. The mandibular ramus measurements were carried out using WebPlot Digitizer v 4.1. The measurement was statistically assessed. Statistical Analysis Used: SPSS version 20 was used for discriminate analysis, correlation, and regression analysis. Results: The male population showed higher values of ramus measurements compared to the female population. A regression equation was positively drawn to estimate the age of the unknown individual. Conclusions: Coronoid height is the main predictive factor in age estimation of an individual irrespective of the gender whereas gonial angle is the extrapolative tool in gender prediction.